Organizational structures within the scope of strategic marketing planning: a discursive study - Toledo, Luciano Augusto (Revista de Administração da UFSM, 2010)
The present article proposes to analyze marketing planning within the context of innovative organizational structures. The work has been structured as an essay, and is comprised of a review of the theoretical reference, set against a conceptual critical analysis of a few aspects pertinent to the theme. Issues around the difference among the several strategic levels, such as the formulation of corporate strategies, competitive and structural. Additionally, marketing planning activities were situated in companies’ structural hierarchizing. Lastly, a reflection is conducted, raising issues adjacent to marketing planning, strategies, and innovative organizational structures.